A simple method for analysis of vitamin A palmitate in fortified cereal products using direct solvent extraction followed by reversed-phase HPLC with UV detection. (15th March 2023) - Van Wayenbergh, Eline; Verheijen, Jolien; Langenaeken, Niels A.; Foubert, Imogen; Courtin, Christophe M.
Graphical abstract: Highlights: A method for the quantification of retinyl palmitate using HPLC-UV was developed. The HPLC method had a low LOD (0.01 µg/mL) and LOQ (0.03 µg/mL). Vitamin A was completely extracted from simple matrices using acetone/methanol. Vitamin A was efficiently extracted from bread and cookies with chloroform/methanol. The newly developed procedure and the standard procedure yielded equivalent results. Abstract: Vitamin A is generally analysed using a time-consuming and possibly detrimental saponification step, followed by extraction and HPLC analysis. We here developed a new method to analyse retinyl palmitate (RP) (also known as vitamin A palmitate) without the need for saponification and validated it in model systems consisting of RP, soy oil and wheat bran, and in RP-fortified cereal products. Two direct solvent extraction protocols using acetone/methanol (7/3, v/v) or chloroform/methanol (1/1, v/v) were tested. After extraction, RP was quantified by reversed-phase HPLC with UV detection. The HPLC method had low limits of detection (0.01 µg/mL) and quantification (0.03 µg/mL). Both extraction protocols showed a good recovery (88–105 %) and intra-and inter-day precision (<5%) for RP extraction from the model systems. The obtained results corresponded to results obtained using a golden standard approach. For complex food matrices like bread and cookies, the chloroform/methanol extraction protocol showed the best performance characteristics.